DIGITAL MARKETING, FINANCIAL TECHNOLOGY, AND MARKET ORIENTATION STRATEGY: A STUDY ON MSME’s MARKETING PERFORMANCE - Austin Alexander Parhusip; Aisyah Azhar Adam (PT. Radja Intercontinental Publishing, 2026)
Culinary MSMEs play a strategic role in the Medan City economy, but the increase in the number of businesses has not always been followed by an increase in marketing performance. This study aims to analyze the influence of digital marketing, financial technology, and market orientation on the marketing performance of culinary MSMEs in Medan City. The study used an associative quantitative approach. The study population was MSMEs in Medan City, with a sample of 100 respondents determined through a purposive sampling technique. Data were obtained through research instruments and analyzed using validity tests, reliability tests, classical assumptions, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results showed that digital marketing had a positive and significant effect on marketing performance. Financial technology also had a positive and significant effect and was the variable with the largest contribution. Meanwhile, market orientation had a positive relationship, but did not have a significant effect partially. Simultaneously, all three variables had a significant effect on the marketing performance of culinary MSMEs in Medan City with an Adjusted R Square value of 0.697. These findings demonstrate the importance of integrating digital promotion, financial technology, and market understanding to strengthen the competitiveness of MSMEs.